Characterization of epitope specificities of reference antibodies used for the quantification of the birch pollen allergen Bet v 1. Issue 5 (12th December 2017) - Brier, S.; Le Mignon, M.; Jain, K.; Lebrun, C.; Peurois, F.; Kellenberger, C.; Bordas‐Le Floch, V.; Mascarell, L.; Nony, E.; Moingeon, P.
Abstract: Background: Accurate allergen quantification is needed to document the consistency of allergen extracts used for immunotherapy. Herein, we characterize the epitope specificities of two monoclonal antibodies used in an ELISA for the quantification of the major birch pollen allergen Bet v 1, established as a reference by the BSP090 European project. Methods: The ability of mAbs 5B4 and 6H4 to recognize Bet v 1 isoforms was addressed by immunochromatography. The capacity of each mAb to compete with patients' IgE for binding to Bet v 1 was measured by ELISA inhibition. Epitope mapping was performed by pepscan analysis, site‐directed mutagenesis, and hydrogen/deuterium exchange‐mass spectrometry. Results: The 5B4 epitope corresponds to a peptide sequence (I56‐K68) overlapping with the binding sites of patients' serum IgEs. Mutation of residues P59, E60, and K65 abolishes 5B4 binding to Bet v 1 and reduces the level of IgE recognition. In contrast, 6H4 recognizes a conformational epitope lying opposite to the 5B4 binding site, involving residues located in segments I44‐K55 and R70‐F79. Substitution of E45 reduces the binding capacity of 6H4, confirming that it is critical for the interaction. Both mAbs interact with >90% of Bet v 1 content present in the birch pollen extract, while displaying a weak cross‐reactivity with other allergens of the PR‐10 family. Conclusions: MAbs 5B4 and 6H4 recognize structurally distinct epitopes present in the vast majority of Bet v 1 isoforms. These results support the relevance as a reference method of the Bet v 1‐specific quantitative ELISA adopted by the European Pharmacopoeia.